The Structure of Agricultural Trade Industry in Developing Countries - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2013)
Expansion of global trade has been heralded as a great boon for agriculture. However, benefits of such expansion has been seen by some quarters as inequitable due to the role of large agribusiness firms and conglomerates. This study synthesizes existing research on the market structure of agro-industry trade. Its key findings are as follows: - The dominance of large-scale operations is more pronounced in the downstream stages. Moreover, distribution for foreign markets is the most concentrated part of the global chain. - Increasing horizontal concentration, and vertical coordination, arises from a set of supply drivers (e.g., technological change), demand drivers (e.g., rising purchasing power), policies, and institutional factors. - There is some evidence for significant market power being exercised among the more concentrated value chains. Furthermore, indications that market concentration can also be leveraged to widen the exercise of market power via coordination along a supply chain. However, the association is not absolute. - At the farm level, the evidence is more solid: size of land asset or scale of production, by itself, does not seem to disqualify smallholders from supplying to consolidated value chains, as there are enabling schemes such as supervised contract growing, cooperatives, farmer associations, and the like. More critical however are human capital, farm management practices, and other assets such as equipment and irrigation facilities.Despite the great volume of relevant literature, the tentative nature of the findings stated above indicate wide scope for further research in this area. Better information and analysis could perhaps pave the way toward design of policies for more equitable and yet productive and efficient global value chains.
Keywords: 330; distribution; agricultural trade; market structure; global value chain